Association of thrombophilia prospective detection with hemocompatibility related outcomes in left ventricular assist device patients. Issue 11 (November 2021) - Konarik, Miroslav; Netuka, Ivan; Ivak, Peter; Riha, Hynek; Tucanova, Zuzana; Wohlfahrt, Peter; Maly, Jiri; Szarszoi, Ondrej
Introduction: Inherited thrombophilias represent a concerning risk factor due to a proclivity to an aberrant clot formation. However, in patients with left ventricular assist device (LVAD), their impact on bleeding and thrombotic complications remains still poorly understood. The aim of the present study was to evaluate the effect of thrombophilic mutation directed anticoagulation therapy on adverse clinical outcomes in LVAD patients. Materials and methods: About 138 consecutive patients indicated for LVAD implant (HeartMate II, Abbott, Plymouth, USA) were prospectively screened for three major thrombophilic mutations: factor II (prothrombin), factor V Leiden, and homozygous methylenetetrahydrofolate reductase (MTHFR). Subsequently, discordant individualized anticoagulation targets of INR 2.5–3.0 in thrombophilia positive and INR 1.8–2.2 in negative patients were established; notably without anti-platelet agents given the center standard of care. Results: Mean age was 50 ± 12.7 years, 83% male. Mean duration of support was 464.5 days (SD 482.9; SEM 41.1) and median of 310 days (IQR 162; 546). Full thrombophilia positive cohort analysis has not revealed any significant impact on event free survival. In contrast, detailed analysis of specific thrombophilias subsets has revealed Factor II prothrombin mutation as a significant predisposition for the pump thrombosis risk (SHR 10.48; p = 0.001) despite more aggressive prespecified anticoagulation target. Moreover, the incidence of bleeding events in prothrombin group was also significantly increased (SHR 6.0; p = 0.03). Conclusions: Our observations suggest that specific thrombophilias in LVAD patients may pose different intensity predisposition for thrombotic complications. Factor II (prothrombin) positive mutation was identified as significant risk factor associated with the pump thrombosis.